An inquiry into the incorporation of a multicultural approach in contemporary textbooks in South Africa - Sharma, Anjali (Rhodes University, Faculty of Education, Department of Education, 2001)
During the past few decades a substantial body of research has emerged in western as well as the developing nations studying the racial bias in children's texts. However, it is only recently in South Africa, with the ascendance of the ANC government, that interest has been focused on eliminating apartheid values and on promoting multicultural tenets in the school curriculum. It is undeniable that the concept of multiculturalism has been severely stigmatised in the South African educational context. Anxieties have been expressed about embracing the discourse of multicultural education within the educational system based on fears that, like the previous educational system, it too will perpetuate group differences. Nevertheless, in recent years, a clear consensus view has emerged that the implementation of multicultural education is imperative if the goal of a rainbow South Africa is to be realised. Against this background, the present study attempts to study the incorporation of a multicultural approach into contemporary textbooks. To realise this aim I selected a sample of four textbooks, one from each of the major disciplines (science, English, geography and history), and SUbjected the texts and pictures from each to content analysis. The findings of this study suggest that a multicultural approach shall at least for the foreseeable future remain a central feature of learning materials produced for the new South African curricula. The findings indicate that multicultural aspects predominate in the texts as compared to other ideologies. This applies to both text content and illustrations. Contrary to the researcher's initial expectation, however, the texts also reveal a strong tendency towards Eurocentric and patriarchal approaches. This research does not conform to traditional, 'scientific' criteria of validity and reliability; it seeks only to investigate textbook material in more depth and thereby contribute to a more comprehensive understanding of the extent to which the texts subscribe to a multicultural approach. Such understanding may help both educationalists and authors in their evaluation of existing textbook material, and in the production of new texts which reflect the reality of South Africa as a multicultural society.
Keywords: Multicultural education -- South Africa; Multicultural education -- Curricula; Textbooks -- South Africa -- Evaluation